Musculoskeletal Radiology Curriculum for the USMLE Step 1: A Digital Atlas of Relevant MRI Anatomy and Case-Based Discussion of Selected Traumatic and Mechanical Disorders - Ezekiel Maloney; Jack Porrino (Association of American Medical Colleges, 2014)
Abstract Introduction This curriculum is designed to educate second-year medical students about the magnetic resonance (MR) appearance of fundamental knee and shoulder anatomy and selected musculoskeletal traumatic and mechanical disorders in preparation for Step 1 of the USMLE. It includes three parts: a scrollable, digital atlas of MR images of the shoulder and knee (and supplementary line drawing highlighting the anatomic course of the ACL and PCL); color-annotated radiographs labeled with important bony and muscular landmarks; and cased-based discussions with interactive multiple-choice questions to review and solidify the image-based anatomy covered in the first two sections, as well as to introduce two-step thinking with targeted radiologic-pathologic correlates. Methods The educational module is ideally introduced in lecture format by a medical faculty member who is familiar with musculoskeletal MR imaging, and is then provided to students for self-directed learning and review; however the module can also be completed by students independently to achieve the same learning objectives. The module employs a multi-modality, interactive, digital approach to anatomic teaching; a technique that has been shown to be effective and valued in the teaching of human anatomy to medical students. Results This module was utilized as a co-curriculum to supplement the USMLE Step 1 review course for second year medical students at the University of Washington. It was presented in lecture format in February of 2014, and the resource was subsequently distributed to students for independent review. The curriculum was well received by the students, who provided multiple positive comments regarding this particular co-curriculum at the conclusion of the formal review course. Discussion Common applications on Step 1 include identification of normal anatomy on cross sectional imaging and radiographs, as well as recognition of basic radiologic-pathologic correlates. Using this as a set of guidelines, we identified specific educational goals for musculoskeletal radiology - including identification of basic cross sectional knee and shoulder anatomy on MRI, as well as musculoskeletal landmarks on radiographs of the shoulder, elbow, hand, hip/pelvis, and knee.